Pemanfaatan Pekarangan Rumah Sebagai Dapur Hidup dengan Teknik Vertikultur Untuk Meningkatkan Ketahanan Pangan Keluarga dan Menambah Eksotik Daerah Wisata - Tangio, Julhim S.; Sihaloho, Mangara; Mohamad, Erni; Laliyo, Lukman A.R; Pikoli, Masrid; Husain, Rustam I; Biallangi, Nurhayati; Ischak, Netty Ino (Damhil: Jurnal Pengabdian kepada Masyarakat, 2025)
Community service activities constitute one of the core mandates (Tri Dharma) of higher education and may be regarded as a key responsibility of institutions, lecturers, and students. A home yard is an open space surrounding a residence. When properly maintained, it can create an attractive, comfortable, healthy, and pleasant environment that enhances residents’ well-being at home. This community service program aimed to optimize the utilization of home yards through a vertical cultivation (verticulture) system using plastic waste, in order to generate additional household income and improve aesthetic value. In addition, the program promoted the reuse and recycling of plastic waste as planting media. The methods employed included field observation, communication of the activity plan, collection of plastic waste, program socialization, counseling, training and group sharing sessions, and finally monitoring. The socialization results demonstrated that used cooking oil packaging could be repurposed into planting containers and beverage bottles could be utilized as verticulture planting media. The main crop emphasized in this program was chili, which is commonly needed in every household. Other crops suitable for verticulture include annual, high-moisture herbaceous plants such as spinach, water spinach (kangkung), and lettuce, as well as tomatoes and other plant species. The implementation of this program motivated community groups to manage household waste into compost and enhanced their knowledge and skills in vegetable and medicinal plant cultivation techniques. As a result, the surrounding environment became cleaner and greener, and community members were able to meet their needs for vegetables and medicinal plants around their homes.